PYROPHOSPHATE AS A SOURCE OF PHOSPHORUS: HYDROLYSIS UNDER DIFFERENT CONDITIONS - Ahmad, Fiaz; Kelso, William Ian (Journal of Research (Science), 2001)
Polyphosphates are occasionally added to the soils as a phosphate source for plant nutrition. Polyphosphates (e.g. pyrophosphates) may be more economical due to their smaller volume and low transportation costs. Pyrophosphates (PP) are water-soluble and their condensed nature results in higher P analyses. However, it is observed that PP is a relatively ineffective source of P for plants prior to hydrolysis to the orthophosphate form. Hydrolysis of PP was, therefore, studied under different conditions. Pyrophosphate hydrolysis proceeded very slowly in solution media compared with that in the soil system. Added orthophosphate (OP), calcium carbonate (CaCO3) and organic acids (rice straw extract) increased PP hydrolysis in solution. Hydrolysis of PP was more in soils subjected to submerged incubations as compared to moist incubations. In soil system addition of OP decreased PP hydrolysis both during submerged and moist incubations, whereas addition of organic acids (rice straw extract) along with OP increased PP hydrolysis. Increasing levels of temperature increased PP hydrolysis both in solution media and in soil system (submerged and moist incubations).